2022
DOI: 10.3389/fpls.2022.1004173
|View full text |Cite
|
Sign up to set email alerts
|

Induction of resilience strategies against biochemical deteriorations prompted by severe cadmium stress in sunflower plant when Trichoderma and bacterial inoculation were used as biofertilizers

Abstract: BackgroundCadmium (Cd) is a highly toxic heavy metal. Its emission is suspected to be further increased due to the dramatic application of ash to agricultural soils and newly reclaimed ones. Thereby, Cd stress encountered by plants will exacerbate. Acute and chronic exposure to Cd can upset plant growth and development and ultimately causes plant death. Microorganisms as agriculturally important biofertilizers have constantly been arising as eco-friendly practices owing to their ability to built-in durability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 151 publications
1
18
0
Order By: Relevance
“…radiata being greatly boosted even in soils with metal contamination. Like our study, after inoculating sunflower plants with Trichoderma sp., Abeed et al claimed that oxidative stress in metal-treated plants declined and antioxidant enzyme activity were significantly reduced. Similarly, combined application of T.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…radiata being greatly boosted even in soils with metal contamination. Like our study, after inoculating sunflower plants with Trichoderma sp., Abeed et al claimed that oxidative stress in metal-treated plants declined and antioxidant enzyme activity were significantly reduced. Similarly, combined application of T.…”
Section: Resultsmentioning
confidence: 99%
“…The evident reduction in antioxidants caused by metal-tolerant fungal inoculation resulted in the overall growth of V. radiata being greatly boosted even in soils with metal contamination. Like our study, after inoculating sunflower plants with Trichoderma sp., Abeed et al 81 claimed that oxidative stress in metal-treated plants declined and antioxidant enzyme activity were significantly reduced. Similarly, combined application of T. asperellum with biochar improved the physiological and oxidative stress properties of Ni- and Cu-stressed Z. mays plants.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that cadmium toxicity had a significant impact on the development and productivity of tomato plants. Several factors are responsible for these decreases [32], including the inhibition of cell division and elongation via the glycolysis pathway [35], the decrease in the mitotic division of meristematic cells [36], the decrease in nutrient uptake and photosynthetic efficiency, which weakens their photosynthetic production capacity, and the increase in production of ROS, which damages the cell membrane and macromolecules [37]. Numerous studies have already shown that Cd has negative effects on tomato plant growth and yield [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In our results, we found that inoculated bermudagrass showed remarkably lower H 2 O 2 levels than uninoculated bermudagrass under P- or K-deficient conditions, indicating that A. aculeatus could significantly attenuate stress-induced oxidative damage. Although plants cannot escape from deleterious environments, they have already developed and established a mathematical regulatory mechanism to cope with stress damage ( Abeed et al., 2022 ). Usually, stress-induced ROS accumulation is scavenged by diverse enzymatic scavengers, such as POD, CAT, SOD, or other antioxidants ( Apel and Hirt, 2004 ).…”
Section: Discussionmentioning
confidence: 99%